Epidemiological Characteristics of Animal Bite Cases Recorded by Case based Surveillance in Iraq 2012 - Muhsen, Thane (AL-Kindy College Medical Journal, 2020)
Background: Animal bite is one of the public health problems all over the world, especially in poor countries. Animal bites have an impact on human health due to rabies disease, which is a viral transmitted disease from animal to human with a high mortality rate.Objective: To determine the epidemiological characteristics of animal bite cases by person, time, and place.Method: Descriptive cross sectional study was done by reviewing cases caused by animal bites., Data including the demographic characteristics of age, gender, occupation, site of bite, and attending health institutions searching treatment were all included.Results: There were 11600 animal bite cases. Most of bites caused by stray dogs 11577(99.8%), and the males were more affected than females. The mostly affected site of bite was lower limbs. Babylon and Naniva provinces registered the highest rate of animal bite victims.Conclusion: The study is determining the epidemiological characteristics of animal bite cases by person, time, place and giving an accurate view about the epidemiological importance of the problem in Iraq.